Counselling Approaches For Mitigating The Psychological Reactions To Covid-19 Pademic in Nigeria - Yusuf, Jamila; A.O., Oniye; Balqis Olabisi, Popoola; H.K., Garba (International Journal of Applied Guidance and Counseling, 2023)
Counseling is a helping profession.  It is an essential part of the response to COVID-19 crisis ravaging the entire globe.  The COVID-19 pandemic poses a major threat to the entire world’s economy and health.  The virus garnered heightened attention from the media.  Individuals may have difficulty delineating between misinformation and authentic information about the disease.  Many individuals and the general public are fearful (or may become fearful) of contracting the novel virus. The psychological reactions to the Covid-19 pandemic in terms of mental health may include stress, anxiety, depression, fear, uncertainty, panic behavior, the feeling of hopelessness, depression, and suicidal behavior.  Counselling is one of the most needed services at this period when the pandemic is ravaging the entire globe.   This paper, therefore, highlighted various counseling approaches such as cognitive behavioral therapy and reframing, solution-focused therapy, meditation and mindfulness, and building emotional resilience for mitigating the psychological reactions to the COVID-19 pandemic. Relevant suggestions were made to further mitigate the psychological reactions of individuals.